Container 1988 - 1989 - 1990 - 1991. - Venturi, Robert; Galleria Container, Firenze (Firenze : Galleria Container, 1991)
Balmes, Guillen ; Battistero, Tenda ; Bersezio, Enzo ; Brunklaus, Nicolette ; Canudas, Jordi ; Cavenago, Umberto ; Daniele, Mario ; Duran i Esteva, Pep ; Duran, Joan ; Haffner, Heidi ; Hiddink, Martin ; Jasci, Alessandro ; Koch, Wilhelm ; Lakke, Allart ; Leegte, Lynne ; Leonardo, Santo ; Mandarino, Andrea ; Mauro, Carlo ; Octave, Jean-François ; Peter, Carl ; Pusole, Pierluigi ; Raynaud, Patrick ; Silva, Luca Da ; Villers, Bernard ; Xiao Xia
alle tentoonstellingen in Galleria Container Firenze in 1988 tot 1991
Italiaans & Engels
boek